Pengembangan Media Belajar Album Stiker Masuk dan Berkembangnya Pengaruh Hindu Budha di Indonesia Sebagai Bahan Ajar Pendukung Mata Kuliah Sejarah Nasional Indonesia I Program Studi Pendidikan Sejarah dan Sosiologi IKIP Budi Utomo Malang - Irvan Lestari; Ari Nugrahani (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
Teaching challenges today require that teachers be able to present interesting learning media innovations. Likewise, in history learning, it is necessary to use innovative media so that students have an interest and interest in historical material. The Indonesian National History course I am a course that allows the use of teaching materials in the form of sticker album media. Broadly speaking, media can be humans, materials, or events that cause students to be able to acquire knowledge, skills or attitudes. The media complements other media in the form of textbooks as well as a learning environment in the form of a campus environment and its infrastructure and facilities. After analyzing the results of interviews and observations, the presence of learning media in the form of sticker albums is quite effective in facilitating lecture activities in general and facilitating the assessment of student assignments in particular. More than that, its presence can make history learning activities not monotonous in the sense that learning activities are centred on lecturers who use the lecture method while students listen passively.Keywords: Learning Media, Sticker Album, History Subject